Retention and characteristics associated with remote questionnaire completion in a general population cohort study: the project baseline health study - Megan K. Carroll; Safa Faheem; Jean Bouteiller; Adrian Hernandez; Kenneth W. Mahaffey; Jessica L. Mega; Neha Pagidipati; Terry Schaack; Svati H. Shah; Sumana Shashidhar; Susan Swope; Donna Williams; et al. (Frontiers in Digital Health)
ObjectiveTo evaluate remote participant engagement in a clinical study over time, based on data from the Project Baseline Health Study (PBHS), a hybrid in-person and virtual study.MethodsThe PBHS enrolled 2,502 adult US residents from March 3, 2017 to April 26, 2019, with a ≤5-year follow-up. We summarized 4-year retention and rates of longitudinal patient-reported outcome survey completion. We investigated participant characteristics for their associations with quarterly remote survey completion using regression models.ResultsOf the total participants (N = 2,502), 94% remained enrolled after 4 years and 60% completed all annual visits; 2,490 participants stayed enrolled for at least one quarter. The median (IQR) number of remote electronic survey sets completed was 8 (3–12), of a possible 16. Age [odds ratio (OR), >70 vs. ≤30 years: 2.56; 95% CI: 2.24–2.94] and education (OR, advanced degree vs. ≤high school: 1.36; 95% CI: 1.22–1.52) were positively associated with remote survey completion. Participants with lower odds of completion were Black (OR vs. White: 0.73; 95% CI: 0.67–0.80), Hispanic (OR vs. non-Hispanic: 0.84; 95% CI: 0.77–0.93), or had at least mild symptoms of depression (OR vs. without: 0.90; 95% CI: 0.84–0.96) or anxiety (OR vs. without: 0.84; 95% CI: 0.78–0.90).ConclusionsOverall, 94% of PBHS participants remained enrolled after four years. Age, race, ethnicity, income, education, and symptomatic depression/anxiety were significantly associated with longitudinal remote questionnaire completion. These findings on engagement over time may inform future longitudinal study design.Clinical Trial RegistrationClinicaltrials.gov, identifier (NCT03154346).